Determination and analysis of harmonic contents in a three-phase installation / Sumaiyah Mohamad Sani - Mohamad Sani, Sumaiyah (2010)
Harmonics generation can lead to serious power quality problem if it is not reduced to acceptable level. Electric components content of non-linear loads contribute to serious harmonics injection to the main supply line. This project is proposed to analyse a harmonic distortion that produced by non-linear loads.